2013
DOI: 10.1139/bcb-2013-0023
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage induced by phenylalanine and its analogue p-chlorophenylalanine in blood and brain of rats subjected to a model of hyperphenylalaninemia

Abstract: Phenylketonuria (PKU) is a disease caused by a deficiency of phenylalanine hydroxylase (PAH), resulting in an accumulation of phenylalanine (Phe) in the brain tissue, cerebrospinal fluid, and other tissues of PKU patients. Considering that high levels of Phe are associated with neurological dysfunction and that the mechanisms underlying the neurotoxicity in PKU remain poorly understood, the main objective of this study was to investigate the in vivo and in vitro effects of Phe on DNA damage, as determined by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…PKU patients’ with severe neurological impairment manifest the following characteristics, such as a direct consequence of neuronal cell loss, synapse reduction, and white matter abnormalities. [ 8 10 ] Studies performed in patients and animal model suggest that the underlying mechanism of pathophysiology has been identified to be related to metabolites accumulation and exert neurotoxic effects on Phe level particularly, which results in DNA damage in patient blood and animal brain subjected to an animal model of PKU [ 11 , 12 ] and cell apoptosis in cultured neurons. [ 13 ] In addition, neuroimaging studies demonstrated high-signal intensity in the periventricular white matter in majority of PKU patients.…”
Section: Discussionmentioning
confidence: 99%
“…PKU patients’ with severe neurological impairment manifest the following characteristics, such as a direct consequence of neuronal cell loss, synapse reduction, and white matter abnormalities. [ 8 10 ] Studies performed in patients and animal model suggest that the underlying mechanism of pathophysiology has been identified to be related to metabolites accumulation and exert neurotoxic effects on Phe level particularly, which results in DNA damage in patient blood and animal brain subjected to an animal model of PKU [ 11 , 12 ] and cell apoptosis in cultured neurons. [ 13 ] In addition, neuroimaging studies demonstrated high-signal intensity in the periventricular white matter in majority of PKU patients.…”
Section: Discussionmentioning
confidence: 99%
“…This inhibitor indeed lowers brain 5-HT levels but it also leads to large depletions of dopamine and norepinephrine [ 50 ]. pCPA also causes an acute hyperphenylalaninemia in rodents and results in cortical DNA damage as soon as 1 hr after treatment [ 51 ]. Drugs that interact with the dopamine and norepinephrine neuronal systems are known to exert powerful effects on sexual behavior in male rodents [ 52 ], making it very difficult to ascribe pCPA-induced changes in sexual preference to 5-HT specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these findings were prevented by supplementation with lipoic acid, melatonin, alpha-tocopherol and/or ascorbic acid, which are potent and well-known antioxidants [22]. Furthermore, in vitro and in vivo DNA damage was found both in patients [32,44] and animal models [45] and it was proposed that it is associated with oxidative damage.…”
Section: Oxidative Stressmentioning
confidence: 99%